Persepsi Guru Baru Bahasa Inggris di Indonesia tentang Penggunaan Penilaian Antar Teman dalam Kelas Berbicara - Wulandari, Ika; Purwati, Oikurema; Setiawan, Slamet; Anam, Syafi'ul (JET (Journal of English Teaching), 2021)
There is convincing evidence of the potential advantages of peer assessment; however, earlier studies on peer assessment in the learning process have largely focused on students’ views on it. Although much can be inferred from the students’ views about peer assessment in the learning process, there is a limited empirical study on the practical use of peer assessment by teachers and their responses. This study attempts to offer salient information for educational institutions, especially on the importance of peer assessment as a part of their instructional design for novice EFL teachers. This qualitative study aims to investigate Indonesian novice EFL teachers’ perceptions of the use of peer assessment in a speaking class as well as its’ benefits and challenges. The data was obtained from six Indonesian novice EFL teachers through a semi-structured interview. Findings revealed the two groups of teachers’ different perceptions, benefits, and challenges of peer assessment which were affected by their understanding of peer assessment and undergraduate study experiences. Hence, educational institutions for pre-service EFL teachers should take peer assessment into account to be integrated into their instructional designs to enable them to experience and perceive peer assessment as a valuable alternative way of language assessment.